Pengaruh Pemasaran Digital dan Brand Positioning terhadap Minat Beli Melalui Kualitas Produk Smartphone Iphone pada Mahasiswa Politeknik Negeri Ujung Pandang - Sumatriani; Amansyah, Farida; Arif, Milda (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2025)
The purpose of this study was to understand perception of digital marketing, to understand perception of Iphone smartphone brand positioning, to understand perception of Iphone smartphone purchase interest, to understand influence of digital marketing on Iphone smartphone product quality, to understand the influence of digital marketing on Iphone smartphone product quality, to understand the influence of brand positioning on Iphone smartphone product quality, to understand the influence of digital marketing on Iphone smartphone purchase interest, to understand the influence of brand positioning on Iphone smartphone purchase interest, to understand the influence of product quality on Iphone smartphone purchase interest, to understand the influence of digital marketing through product quality on Iphone smartphone purchase interest, and to understand the influence of brand positioning through product quality on Iphone smartphone purchase interest. The population of this study was students of the State Polytechnic of Ujung Pandang with a sample of 98 students using validity and reliability tests with quantitative research type. Data analysis uses descriptive and inferential analysis, structural model analysis (Inner model), measurement model analysis (Outer model) and hypothesis testing with the help of SmartPLS 4.0 software. Base on the result of research conducted that digital marketing has a positive and significant effect on product quality, brand positioning has a positive and significant effect on product quality, digital marketing has a positive and significant effect on buying interest, brand positioning has a positive and significant effect on buying interest, brand positioning has a positive and significant effect on buying interest, digital marketing can affect buying interest through intervening variables, namely product quality and brand positioning can affect buying interest through intervening variable, namely product quality.